Digital single-operator pancreatoscopy for the treatment of symptomatic pancreatic duct stones: a prospective multicenter cohort trial - Gerges, Christian; Albers, David; Schmitz, Lukas; Goni, Elisabetta; Cappello, Annalisa; Schirra, Jörg; Casper, Markus; Dormann, Arno J.; Hartmann, Dirk; Hollenbach, Marcus; Schneider, Markus; Denzer, Ulrike W.; Dechene, Alexander; Dollhopf, Markus; Mayerle, Julia; Schumacher, Brigitte; van Geenen, Erwin-Jan M.; Neuhaus, Horst; Siersema, Peter D.; Ellrichmann, Mark; Beyna, Torsten; on behalf of the German Cholangioscopy Group; Weismüller, Tobias; Arlt, Alexander; Schlag, Christoph; Hampe, Jochen; Kandulski, Arne; Hoffmann, Arthur (Endoscopy, 2022)
Background Digital single-operator pancreatoscopy (DSOP)-guided lithotripsy is a novel treatment modality for pancreatic endotherapy, with demonstrated technical success in retrospective series of between 88 % and 100 %. The aim of this prospective multicenter trial was to systematically evaluate DSOP in patients with chronic pancreatitis and symptomatic pancreatic duct stones.Methods Patients with symptomatic chronic pancreatitis and three or fewer stones ≥ 5mm in the main pancreatic duct (MPD) of the pancreatic head or body were included. The primary end point was complete stone clearance (CSC) in three or fewer treatment sessions with DSOP. Current guidelines recommend extracorporeal shock wave lithotripsy (ESWL) for MPD stones > 5 mm. A performance goal was developed to show that the CSC rate of MPD stones using DSOP was above what has been previously reported for ESWL. Secondary end points were pain relief measured with the Izbicki pain score (IPS), number of interventions, and serious adverse events (SAEs). Results 40 chronic pancreatitis patients were included. CSC was achieved in 90 % of patients (36/40) on intention-to-treat analysis, after a mean (SD) of 1.36 (0.64) interventions (53 procedures in total). The mean (SD) baseline IPS decreased from 55.3 (46.2) to 10.9 (18.3). Overall pain relief was achieved in 82.4 % (28/34) after 6 months of follow-up, with complete pain relief in 61.8 % (21/34) and partial pain relief in 20.6 % (7/34). SAEs occurred in 12.5 % of patients (5/40), with all treated conservatively. Conclusion DSOP-guided endotherapy is effective and safe for the treatment of symptomatic MPD stones in highly selected patients with chronic pancreatitis. It significantly reduces pain and could be considered as an alternative to standard ERCP techniques for MPD stone treatment in these patients.